Native CuA Redox Sites are Largely Resilient to pH Variations within Physiological Range - Álvarez Paggi, Damián Jorge (2013)
Previous studies on engineered CuA centres have shown that one of the histidine ligands is protonated and dissociated from the metal site at physiological pH values, thus suggesting a role in regulating proton-coupled electron transfer of cytochrome c oxidases in vivo. Here we report that for native CuA such protonation does not take place at physiologically relevant pH values and, furthermore, no significant changes in the spectroscopic and redox properties of the metal site occur at low pH.